Analyzing the Tensile Strength of AISI 1045 Coil Springs in Avanza 2020 Cars: A Comparative Study of Experimental Results using Simulation Technology - Azhar (Yayasan Kawanad, 2022)
One of the tests used to determine the mechanical properties of metals is the tensile test. The results obtained from the tensile test are crucial for engineering and product design as they provide data on the strength of materials. AISI 1045 carbon steel is an alloy steel composed of iron (Fe) and carbon (C), where iron is the base element and carbon is the main alloying element. Carbon steel is also used in the manufacturing of helical/coil springs (Mobil Alvanza 2020). Coil springs are widely used in the front suspension of modern light vehicles. A new approach to fatigue prediction based on a combination of FE simulation using ABAQUS is opposed in this study. In this research, the tensile test was performed using experimental and ABAQUS simulation methods. The experimental results showed a yield strength of 350.25 MPa and an ultimate tensile strength of 560.4 MPa, while the ABAQUS simulation results showed a yield strength of 356.05 MPa and an ultimate tensile strength of 560.39 MPa